Analysis of impact on IT personnel of outsourcing IT services in organization: a case study of procurement of IT services for “maintenance, upgradation and support services for BRTA-IS” in Bangladesh Road Transport Authority (BRTA) - Khalil, Md. Ibrahim (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.